The Analysis of Formative Assessment in Islamic Religious Education as a Reflective Tool in the Merdeka Curriculum at SMP Negeri 2 Pagar Alam - Utami, Eka; Heriyah Oktaviani (The Future of Education Journal, 2025)
This study aimed to analyze the implementation of formative assessment in Islamic Religious Education subjects as a reflection tool in the Independent Curriculum at SMP Negeri 2 Pagar Alam. The method used in this research was field research with a qualitative descriptive approach, employing data collection techniques such as observation, interviews, and documentation. The results showed that Islamic Religious Education teachers at SMP Negeri 2 Pagar Alam had implemented various forms of formative assessment, such as short quizzes, daily reflections, and multiple-choice questions. However, there were still several obstacles, including time constraints, limited teacher readiness, varied understanding of the formative assessment concept, and a lack of in-depth training. The study concluded that formative assessment played an important role in supporting the success of the Independent Curriculum, but its implementation needed to be improved through continuous training and mentoring for educators.